2007
DOI: 10.1080/08860220701392231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Criteria for the Diagnosis of Balkan Endemic Nephropathy

Abstract: Background. The diagnosis of Balkan endemic nephropathy (BEN) is often made using Danilovic's criteria. The aim of this study was to determine the prevalence, sensitivity, specificity, and predictive value of Danilovic's criteria and several additional indices. Methods. The study included 19 BEN patients, 23 BEN-suspected patients, 34 patients with other kidney diseases, and 23 healthy controls. The sensitivity and specificity of Danilovic's criteria was calculated, and these criteria, in addition to age, sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…Interestingly, analyses odds ratios and P values were much more in favor of a-1 than b-2 microglobulin. Other works evaluated diagnostic criteria for the diagnosis of EN and concluded that a-1 microglobulinuria significantly discriminated EN from other kidney diseases (50,51). Finally, in our cohort with .2000 enrolled farmers, we obtained the same results (42).…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, analyses odds ratios and P values were much more in favor of a-1 than b-2 microglobulin. Other works evaluated diagnostic criteria for the diagnosis of EN and concluded that a-1 microglobulinuria significantly discriminated EN from other kidney diseases (50,51). Finally, in our cohort with .2000 enrolled farmers, we obtained the same results (42).…”
Section: Discussionsupporting
confidence: 76%
“…Although we have not found any coding differences or RNA expression differences in the AMBP gene between the C57BL/6J and DBA/2J strains, the AMBP gene is noteworthy because tubular low-molecularweight proteinuria, in particular, urinary A1M, is a hallmark of BEN, an environmental disease resulting from chronic dietary exposure to AA (26). The elevation of urinary A1M has been proposed as a specific biomarker of early stage BEN (17,22,55). Elevated urinary A1M is believed to be symptomatic of proximal tubule dysfunction.…”
Section: Discussionmentioning
confidence: 87%
“…The different criteria used across various countries to establish a diagnosis of EN and to classify the endangered population make an exact comparison of the EN prevalence between different endemic areas difficult to achieve [16,18,20,[23][24][25][26][27][28] . In Croatia, the modified WHO criteria have been used for the last 4 decades.…”
Section: Methodsmentioning
confidence: 99%